Strategy For Developing The Santripreneur Ecosystem In East Java To Face The 5.0 Era - Khusnudin, Khusnudin; Zuraidah, Zuraidah; Syahirul Alim (Cita konsultindo, 2024)
This study aims to provide a comprehensive overview of the key factors determining the success of santripreneurs in achieving sustainable competitiveness and prosperity. Success is measured by the santripreneur's ability to create competitive advantages that ensure business continuity. The study employs a descriptive quantitative approach with validity and reliability tests using SPSS 25.0, followed by hypothesis testing with SmartPLS 2.0. Data were collected through questionnaires distributed to 100 respondents from five Islamic boarding schools (pondok pesantren) in East Java, Indonesia, where students have been trained in entrepreneurship. The findings reveal that education, experience, strategy, innovation, and successful entrepreneurship are the main factors influencing the entrepreneurial success of santripreneurs. These results contribute to understanding how small, medium, and large enterprises can leverage these factors to achieve business success. Based on the analysis of the determination coefficient, the R Square value for the simultaneous effect on entrepreneurship is 0.808, with an adjusted R Square of 0.804, indicating a significant probability. And the results of the t-statistical test were >1.96 with a significance level of p-value of 0.05 (5%) and a positive beta coefficient. These insights can be applied by novice entrepreneurs as they establish and grow their businesses.